A two-herb formula inhibits STAT3 signaling and exerts anti-melanoma effects in cell and animal models. (25th March 2021) - Li, Jun-Kui; Chou, Ji-Yao; Yin, Cheng-Le; Fu, Xiu-Qiong; Wu, Ying; Chen, Ying-Jie; Bai, Jing-Xuan; Wu, Jia-Ying; Liang, Chun; Yu, Zhi-Ling
Abstract: Ethnopharmacological relevance: Malignant melanoma is a fatal cancer. Signal transducer and activator of transcription 3 (STAT3) has been proposed as a therapeutic target of melanoma. An herbal formula Huai-Hua-San (HHS) comprising Sophorae Flos (SF) and Gardeniae Fructus (GF) is traditionally used for treating cancers including melanoma, but the pharmacological basis is unknown. Aims of this study: This study aimed to investigate the anti-melanoma effects of an ethanolic extract of HHS (HHSE), and explore the involvement of STAT3 signaling in the effects. Materials and methods: An UPLC-TOF/MS method was developed to control the quality of HHSE. A B16F10 allograft mouse model and three melanoma cell lines (B16F10, A375 and A2058) were used to determine the anti-melanoma effects of HHSE. Dacarbazine (DTIC) and Stattic were used as positive controls. Cell viability was detected using MTT and crystal violet staining assays. Cell apoptosis was analyzed by flow cytometry after the cells were stained with Annexin-V/PI. Cell invasive ability was examined using the transwell assay. Protein levels were determined by Western blotting. Results: The contents of crocin I, crocin II, quercetin and kaempferol in HHSE were 0.59%, 0.98%, 4.66% and 1.15%, respectively. A clinically relevant dose of HHSE (0.1 g/kg/day, i.g. for 15 consecutive days) significantly suppressed B16F10 tumor growth in mice. HHSE dose-dependently reduced cell viability and dampened invasion of, and induced apoptosis in, melanoma cells. Mechanistic studies revealed that HHSE inhibited the phosphorylation/activation of STAT3 in B16F10 allografts and in cultured melanoma cells. In cell models, HHSE also inhibited the phosphorylation of STAT3 upstream kinases, JAK2 (Tyr1007/1008) and Src (Tyr416), lowered STAT3 nuclear levels, and down-regulated the protein levels of STAT3-targeted molecules. Over-activation of STAT3 in A375 cells significantly attenuated the cytotoxic effects of HHSE. Conclusions: HHSE exhibits anti-melanoma effects in cell and mouse models. Inhibition of STAT3 signaling contributes to the anti-melanoma mechanisms of HHSE. Our findings lay a groundwork for developing HHSE as a modern agent for melanoma management, and provide pharmacological justifications for the traditional use of HHS in treating melanoma. Graphical abstract: Image 1